THE EFFECTIVENESS OF THE ALEF DIGITAL CONTENT IN ENHANCING JUNIOR HIGH SCHOOL STUDENTS’ MATHEMATICAL UNDERSTANDING OF EXPONENTS - Ulfa, Maria; Chairuddin, Chairuddin; Sari, Dian Ulfa (JME (Journal of Mathematics Education), 2025)
The integration of digital content in mathematics learning has become increasingly important to improve students’ engagement and conceptual understanding. This study aims to determine the effectiveness of using ALEF Education content on students’ mathematical understanding of exponents at SMP Negeri 1 Kolaka. This research employed a quantitative approach with a quasi-experimental design (post-test only control group), involving 48 eighth-grade students divided into an experimental and a control class. The experimental group learned using ALEF Education content integrated into classroom instruction, while the control group received conventional lessons without digital media. Data were collected through observations of teacher and student activities, as well as a mathematical comprehension test. The results showed that both teacher and student activities in the experimental class were higher (teachers: 84%; students: 80%) than in the control class (teachers: 81%; students: 72%). Students in the experimental group also achieved higher post-test scores (M = 19.54) than those in the control group (M = 19.48), and statistical analysis confirmed that the difference was significant at the 0.05 level. These findings indicate that ALEF Education content effectively improves students’ mathematical understanding and engagement in learning exponents. Integrating interactive and adaptive digital content into mathematics learning can thus serve as an innovative alternative to achieve meaningful and technology-enhanced learning outcomes in the 21st-century classroom.